2021
DOI: 10.1051/0004-6361/202039563
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength constraints on the unidentified Galactic TeV sources HESS J1427−608, HESS J1458−608, and new VHE γ-ray source candidates

Abstract: Aims. Among the γ-ray sources discovered at high and very-high energies, a large fraction still lack a clear identification. In particular, the H.E.S.S. Galactic Plane Survey (HGPS) revealed 78 TeV sources among which 47 are not clearly associated with a known object. Multiwavelength data can help identify the origin of the very-high energy γ-ray emission, although some bright TeV sources have been detected without clear counterparts. We present a multiwavelength approach to constrain the origin of the emissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…emission region and has a hard, pulsar-like spectrum which connects smoothly to the TeV γ−ray spectrum measured by H.E.S.S. Although the exact mechanism responsible for the generation of γ−ray emission is not yet clear, Devin et al [28] conclude that the presence of coincident, extended X-ray emission region and the hard spectral shape of the Fermi-LAT source suggests a leptonic scenario. In this scenario, the TeV γrays are generated by inverse Compton scattering of lowenergy photons by relativistic non-thermal electrons or positrons.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…emission region and has a hard, pulsar-like spectrum which connects smoothly to the TeV γ−ray spectrum measured by H.E.S.S. Although the exact mechanism responsible for the generation of γ−ray emission is not yet clear, Devin et al [28] conclude that the presence of coincident, extended X-ray emission region and the hard spectral shape of the Fermi-LAT source suggests a leptonic scenario. In this scenario, the TeV γrays are generated by inverse Compton scattering of lowenergy photons by relativistic non-thermal electrons or positrons.…”
supporting
confidence: 53%
“…Multiple groups have attempted to estimate the age of HESS J1427-608. Assuming that the TeV source is an evolved PWN, Devin et al [28] estimate a characteristic age between 4.9−13.6 kyr. Fujinaga et al used the correlation between the ratio of γ−ray to X-ray flux (F γ /F X ) and τ c to obtain τ c ∼ 6.4 kyr [84].…”
Section: Coherence Timementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the extension of HESS J1843-033 in the TeV range can be explained by ICS off the CMB photons by ;10 TeV electrons diffusing for ∼8 kyr. Devin et al (2021) found no radio or X-ray emission that indicates the existence of a PWN. Given the characteristic age of PSR J1844-0346, synchrotron emission from the PWN would not be bright enough to be observed owing to the decay of the magnetic field (Tanaka & Takahara 2010).…”
Section: Discussionmentioning
confidence: 94%
“…This pulsar, also named 4FGL J1844.4-0345 (Abdollahi et al 2020), was discovered by Fermi-LAT (Clerk et al 2017), and its spin-down luminosity, characteristic age, and spin period are 4.2 × 10 36 erg s −1 , 12 kyr, and 113 ms, respectively. Assuming that the distance to the pulsar is 4.3 kpc (Devin et al 2021), the gamma-ray energy flux of 1.1 × 10 −11 erg cm −2 s −1 in 1 TeV < E < 10 TeV (H.E.S.S. Collaboration 2018a) is translated into the luminosity of 2.4 × 10 34 erg s −1 .…”
Section: Discussionmentioning
confidence: 99%